Parapneumonic pleural effusion: early versus late thoracoscopy - Pereira,Rodrigo Romualdo (2017)
ABSTRACT Objective: To evaluate the best time to perform thoracoscopy for the treatment of complicated parapneumonic pleural effusion in the fibrinopurulent phase in patients ≤ 14 years of age, regarding the postoperative evolution and occurrence of complications. Methods: This was a retrospective comparative study involving patients with parapneumonic pleural effusion presenting with septations or loculations on chest ultrasound who underwent thoracoscopy between January of 2000 and January of 2013. The patients were divided into two groups: early thoracoscopy (ET), performed by day 5 of hospitalization; and late thoracoscopy (LT), performed after day 5 of hospitalization. Results: We included 60 patients, 30 in each group. The mean age was 3.4 years; 28 patients (46.7%) were male; and 47 (78.3%) underwent primary thoracoscopy (no previous simple drainage). The two groups were similar regarding gender, age, weight, and type of thoracoscopy (p > 0.05 for all). There was a significant difference between the ET and the LT groups regarding the length of the hospital stay (14.5 days vs. 21.7 days; p < 0.001). There were also significant differences between the groups regarding the duration of fever in days; the total number of days from admission to the initiation of drainage; and the total number of days with the drain in place. Eight patients (13.6%) had at least one post-thoracoscopy complication, there being no difference between the groups. There were no deaths. Conclusions: Performing ET by day 5 of hospitalization was associated with shorter hospital stays, shorter duration of drainage, and shorter duration of fever, although not with a higher frequency of complications, requiring ICU admission, or requiring blood transfusion.